Cephalometric Evaluation in Patients with Obstructive Sleep Apnea undergoing Lateral Pharyngoplasty - Zanco, Stephanie Regiane Prata Ferreira; Duarte, Bruno Bernardo; Almeida, Aurélio Rochael; Mendonça, José Alexandre (International Archives of Otorhinolaryngology, 2024)
Introduction Lateral pharyngoplasty (LP) has shown promising results. Craniofacial deformity reduces the pharyngeal space, contributing to the etiopathogenesis. The analysis of craniofacial features can be performed using cephalometry.Objective To verify if craniofacial deformity is associated with worse polysomnographic data in patients with obstructive sleep apnea (OSA), and to verify if the preoperative cephalometric parameters can interfere with the surgical success of the LP.Methods The study included 21 patients with OSA aged between 18 and 65 years who underwent LP in a university hospital from 2015 to 2019. Polysomnography was performed postoperatively, after a minimum period of 6 months from the surgical procedure. In addition, a cephalometric evaluation was performed to assess craniofacial deformity, and to correlate it with the polysomnographic results.Results The mean and median of all polysomnographic respiratory parameters improved postoperatively, especially the apnea-hypopnea index (AHI), which went from 40.15 to 16.60 events per hour (p = 0.001). Of the 21 patients, 15 showed improvements in the AHI postoperatively. As for the cephalometric evaluations, we found that the longer the distance between the hyoid bone and the mandibular plane, the greater the patient's preoperative AHI (p = 0.011). When assessing whether cephalometric changes related to craniofacial deformities influence the surgical outcome of LP, no correlation was found for any cephalometric measurement.Conclusion The longer the distance between the hyoid bone and the mandibular plane, the greater the preoperative AHI, and LP was an effective OSA treatment. Cephalometric variables are not able to modify or determine the success of LP in apneic patients in the population assessed.
Keywords: craniofacial abnormalities; sleep apnea syndrome; cephalometrics